Economic Impact of Tourism on the Host Community in Kerala - A. D. Rajeev Kumar and S.V. Sudheer (Commerce Spectrum, 2015)
Kerala, a lush green strip of land located in the South West corner of Indian peninsula, enjoys a prominent place in the world tourism map. An assortment of tourist centres scattered over the different regions of the state has influence on the host population in terms of income and socio-economic development. Host community is bestowed with ample opportunities to generate economic benefits directly and indirectly from tourism. Business is the major activity available for the host community to get economic benefits directly from tourism. Even though host community engaged in tourism-related business is expected to derive economic benefits, they may not be economically benefited or the benefits available for them may not be sufficient enough in bringing improvement to their economic conditions. This necessitates the need for studying whether traders and businessmen belonging to host community is really benefited or not in economic terms. The question of whether these economic benefits have contributed for improving their economic conditions is also to be validated. The findings of the study endorse that host community engaged in various tourism-related businesses is economically benefited and these benefits make significant contributions in improving their economic conditions.